Economic impact of maize research in Tanzania - Moshi, A.J.; Anandajayasekeram, P.; Kaliba, A.; Martella, D.; Mwangi, W.; Shao, F.M. (CAB International, 2007)
Maize was introduced in Tanzania in the 16th century but research on appropriate varieties and management practices did not get underway until the 1940s. In 1974, a National Maize Research Program (NA{RP) was established to co-ordinate maize research. During 1974-1994 the NM RP released 15 varieties. This study was conducted to assess the socio-economic impact of maize technology Development and transfer investment from 1974 to 1994. Standard pre-tested questionnaire and multi-stage sampling procedures were used for primary data collection. Data were collected from 978 farmers in 53 sites across seven agroecological zones. The sample survey revealed that the adoption rate of the improved varieties for the various zones were 28%, 66%, 44%, 24%, 66%, 81 % and 36% for the Central, Eastern, Lake, Northern, Southern, Southern Highlands and the Western Zones, respectively. The study demonstrated that farmers adopt the cheapest and low-risk technological components in a stepwise process reflecting the profitability and riskiness of each component. The estimated rate of return for the maize research and Development in Tanzania was 19%.